125I inhibits the progression of cervical cancer by upregulating the HSF1/PU.1/SYK signaling pathway and consequently enhancing the apoptotic response mediated by ROS/USP7/P53 - Xiaomei Fan; Xiaoliang Liang; Yunfeng Guo; Ge Jin; Dong Ming; Xingwei An (Scientific Reports)
Abstract 125I (iodine-125) is a radioactive isotope commonly used in the treatment of cervical cancer, especially in brachytherapy. This study investigates the molecular mechanism by which 125I radiotherapy inhibits the progression of cervical cancer. C33A cervical cancer cells were subjected to irradiation with 125I. Subsequently, lentiviral infection was utilized to overexpress and knock down HSF1, as well as to overexpress PU.1. The efficiency of gene knockdown was evaluated via qPCR experiments, followed by treatment with the SYK inhibitor R406. Immunofluorescence staining was employed to determine the relative fluorescence intensity of HSF1 and P53. The relative protein expression levels of HSF1, PU.1, SYK, Dectin-1, and P53 were assessed using flow cytometry to examine apoptosis in C33A cells. Cell viability and proliferative capacity were measured using CCK-8 assays and colony formation assays. The progression of cervical cancer was evaluated through subcutaneous xenograft tumor experiments in nude mice. Transwell and scratch assays were conducted to assess the invasive and migratory capabilities of C33A cells. 125I radiotherapy can augment the expression of HSF1, PU.1, SYK, Dectin-1, β3-integrin, P22, P47, P53, gp91, and p-USP7 in C33A cells. In subcutaneous xenograft tumor experiments conducted in nude mice, 125I radiotherapy also facilitates apoptosis in C33A cells, curtails their viability, proliferative potential, and invasive and migratory capacities, thereby mitigating the progression of cervical cancer. However, specific knockdown of HSF1 and the administration of the SYK inhibitor R406 can reverse the potentiating effect of 125I radiotherapy on the ROS/USP7/P53 pathway, consequently promoting the progression of cervical cancer; specific overexpression of PU.1 can abrogate the inhibitory impact of HSF1 knockdown on the ROS/USP7/P53 pathway, thereby suppressing the progression of cervical cancer. 125I inhibits the progression of cervical cancer by upregulating the HSF1/PU.1/SYK signaling pathway and consequently enhancing the apoptotic response mediated by ROS/USP7/P53.